Discussing community participation in health: an approach from the Brazilian experience Discutindo a participação comunitária na saúde: uma abordagem a partir da experiência brasileira - Romulo Maciel Filho; José Luiz C. de Araújo Jr (Instituto Materno Infantil de Pernambuco, 2002)
This article deals with the problem of community participation in the process of planning, management and decision-making in the Brazilian health system. It seeks to discuss the political process that gave rise to the formation of this model of participation in Brazilian health sector and to identify the reasons for possible weaknesses or constraints in the functioning participatory process.To that end, it makes a review on the literature to address the concept and approaches related to community participation, the advantages of adopting it, some obstacles to its implementation in health management and planning, as well as identifying three kinds of participation in health, according to different technical-political practices and rationalities. Special attention is given to Brazilian experiments in health participation, which culminated in the institutionalising of health councils. In this sense, emphasis is placed on the importance of the social process known as the "Health Reform Movement" and on the holding of the VIII National Health Conference in 1986. Finally, the study concludes that in countries with political, social and economic characteristics like Brazil, the task of incorporating community participation in the formulation and management of health policy depends on the creation of a new spirit of citizenship. Este artigo lida com o problema da participação comunitária no processo de planejamento, gestão e tomada de decisões no sistema de saúde brasileiro. Procura discutir o processo político que possibilitou a conformação desse modelo de participação no setor saúde do Brasil e identifica razões para possíveis debilidades ou limitações no sistema participativo em funcionamento. Para este fim, foi realizada uma revisão na literatura cercando o conceito e as distintas abordagens relacionadas à participação comunitária, as vantagens em se adotar tal prática, os obstáculos para sua implementação na gestão e planejamento da saúde. Essa revisão também identifica três tipos de participação em saúde, relacionadas a diferentes racionalidades e práticas técnico-políticas. Atenção especial é dada aos experimentos brasileiros de participação em saúde que culminaram na institucionalização dos conselhos de saúde. Neste sentido enfatiza-se a importância do processo social conhecido como "Movimento pela Reforma Sanitária" e a realização da VIII Conferência Nacional de Saúde em 1986. Finalmente, o estudo conclui que em países com características políticas e socioeconômicas que guardem semelhanças com o Brasil, a tarefa de incorporar participação comunitária na formulação e gestão da política de saúde depende da criação de um novo espírito de cidadania.